İsmail Gasprinski'nin tercüman'ı : Sadakat ve Terakki (1883-1914) - Karabulak, Ozan (My University, 2024)
Kırımlı İsmail Mirza Gasprinski (1851-1914) tarafından Bahçesaray’da neşredilen Tercüman (1883-1918) gazetesi Rusya Türklerinin en uzun ömürlü ve yaygın süreli yayınıdır. Naşir ve muharriri İsmail Gasprinski’yi aşıp onun en büyük ve etkili eseri haline gelen Tercüman, bu araştırmanın hem öznesi ve çerçevesi hem de temel kaynağı olmuştur. Gazete, eğitimde modernleşmeyi simgeleyen ve başlangıçta eğitsel bir yöntem olarak ortaya çıkıp ardından “Ceditçilik” ismiyle kültürel ve politik bir harekete evrilen “Usul-i Cedid”in çok uzun yıllar en önemli propaganda aracı olduğu gibi hitap ettiği okur kitlesi için ortak, sade ve edebî bir dil oluşturma çabasının da somut bir örneğiydi. Çalışmanın içeriği de bu çerçevede şekillendi. Tercüman’ın amacı, yaygınlığı, faydaları gibi açılardan incelenip biçim özellikleri ile toplumsal etkisinin ortaya çıkarılmaya çalışıldığı birinci bölümü Gasprinski’nin Rusya Türkleri için tasarladığı “terakki” projesinin ana hatlarının ele alındığı ikinci bölüm takip etmektedir. Usul-i Cedid ile eğitimin modernleştirilmesi ve ortak edebî dil yaratma gayretinin anlatıldığı bölümlerden sonra Gasprinski’nin Rusya Türklerini yaşadıklarını ülkenin eşit yurttaşı haline getirme arzusu “sadakat” teması ekseninde incelenmiştir.

The newspaper Terjuman/ Perevodchik (1883-1918), published in Crimea/ Bakhchysarai by the Crimean Ismail Mirza Gasprinskii (1851-1914), is the longest-lasting and most widespread periodical of the Turks of Russia. Terjuman/ Perevodchik, which surpassed its editor and publisher Ismail Gasprinskii and became his greatest and most influential work, has been both the subject and framework of this research and its main source. The newspaper was the most important propaganda tool of the “Usul-i Jadid”, which symbolised modernisation in education and initially emerged as an educational method and then evolved into a cultural and political movement with the name “Jadidism”, for many years, and was also a concrete example of the effort to create a common, simple and literary language for the readership it addressed. The content of this study was shaped within this framework. The first part, in which Tercüman is analysed in terms of its purpose, prevalence and benefits and its social impact is tried to be revealed, is followed by the second part in which the main outlines of Gasprinskii's “progress” project for the Turks of Russia are discussed. After the chapters on the modernisation of education with Usul-i Jadid and the effort to create a common literary language, Gasprinskii's desire to make the Turks of Russia equal citizens of the country in which they lived is examined on the axis of the theme of “loyalty”.
Keywords: Ceditçilik Ismail Mirza Gasprinskii; Crimea; İsmail Gaspıralı; İsmail Mirza Gasprinski; Jadidism; Kırım; Perevodchik; Periodicals; Rusya Müslümanları; Rusya Türkleri; Süreli yayınlar; Tatar basını; Tatar Jadidist press; Tatar journalism; Tercüman; Terjuman; The Muslim of Russia; the Turks of Russia; Turks; Türkler; Ukraine; Ukrayna